Students’ Perception of Translation Software: A Case Study in the Bachelor and Master Programs of Arabic Education - M Sholih Salimul Uqba; Hasaniyah, Nur; Al Anshory, Abdul Muntaqim; Mudinillah, Adam (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2024)
This study investigates the perceptions of bachelor and master students of Arabic Language Education towards the use of translation software in higher education, focusing at the State Islamic University of Maulana Malik Ibrahim Malang. The method used is a descriptive qualitative approach, with a questionnaire design and interviews to gain an in-depth understanding of students’ views. The collected data underwent 4 stages of analysis: data collection, data reduction, data presentation and conclusion drawing. The findings show that almost all students use software in translating and doing assignments, with varying portions of use. This happens because they feel helped by the software in doing various assignments easily and quickly, even though also realize that various software is very prone to errors. Students realize that the software allows them to be lazy to translate manually as well as the potential for dependence in its use. Consequently, the translation results generated by the software must be readjusted to the context of the sentence or paragraph being translated. The implication is the need for a cautious approach to the use of translation software in higher education, with an awareness of the limitations of such software, as well as the importance of manual language skill development.